A new species of Aegla Leach, 1820 (Crustacea, Anomura) from the Iguaçu River basin, Brazil - Páez, Fernanda Polli; Marçal, Ingrid Costa; Souza-Shibatta, Lenice; Gregati, Rafael Augusto; Sofia, Silvia Helena; Teixeira, Gustavo Monteiro (Zootaxa, 2018)
A new species of aeglid crab, Aegla okora n. sp., is described. This species was found in the Iguaçu River basin in Paraná state, southern Brazil. Aegla okora n. sp. was discriminated based on morphological and molecular data (mitochondrial COI). Morphologically, the new species differs from congeners of the same river basin by the presence of a trapezoidal areola and the ventromesial border of the ischium having three tubercles, besides other exclusive additional morphological characteristics. Molecular results demonstrated that there is no overlap between the intraspecific distances of Aegla okora n. sp. and the interspecific distance of other species of Aegla added to the analysis, confirming the separation of species and increasing the known diversity of the Iguaçu River basin.